Non-volant mammals of Guanajuato, Mexico: historic review and updated taxonomic list - Sanchez Herrera, Oscar; Magaña-Cota, Gloria; Téllez-Girón, Guadalupe; López-Forment, William; Urbano Vidales, Guillermina (Acta Universitaria, 2014)
In this contribution we review non-flying mammals of the Mexican state of Guanajuato, with an historic perspective and also with the aim of providing a commented taxonomic update. The main sources of data for this work were specialized publications; we reviewed literature from the XIX Century to 2012. Information on museum specimens in Mexico and elsewhere was also considered for an overall assessment of this mammal assemblage. Information thus gathered allowed for a brief diagnosis of the current state of knowledge of this state fauna, and for the identification of aspects requiring further investigation. The updated taxonomic list of non-flying mammals of Guanajuato includes 62 species. An appendix provides information about specimens and the museums where they are housed.
Keywords: Array; Array; Array; Array; Array